Sitotoksisitas pemutih gigi berdasarkan konsentrasi bahan - Mardiana A. Adam (Journal of Dentomaxillofacial Science, 2010)
The aim of this study was to evaluate the cytotoxicity of several tooth whitening material, carbamide peroxide 10%, 15%, 20% and hydrogen peroxide 38% toward BHK-21 cell using MTT assay. Each well of microplates which used for the test were aliquotted BHK21